ENT 530 Social Media Portfolio / Wan Nurfarhaini Wan Mohd Fazli - Wan Mohd Fazli, Wan Nurfarhaini (2019)
The assignment is the study on how to run a business using social media platform. I choose to run a business of selling hijab for Muslimah. In running this business, I learned something new which is how to promote the products using Facebook. Facebook is a strategic platform for entrepreneurs to market their products or services as it is a networking and e-commerce site. I also learned on how to create sales posting such as teaser, soft sell and hard sell with a good copywriting. An effective "soft sell" can help entrepreneurs in answering customers' enquiries.